Voltammetric Determination of Paracetamol with Carbon Paste Electrode Modified with Molecularly Imprinted Electropolymer - I Wayan Tanjung Aryasa; Indra Noviandri (Universitas Jenderal Soedirman, 2022)
Paracetamol is a commom analgesic and antipyretic drug which used for reliefing fever and head ache. The determination of paracetamol dose in pharmaceuticals is very important, becauce an overdose can cause fulminating hepatic necrosis and other toxic effects. Therefore, it is necessary to measure the dose of paracetamol for the patient with precision to avoid harm. Many analytical methodologies have been proposed for determination of paracetamol dose. One of the methods was developed in the past two decades. Generally, electroanalytical approach especially voltammetry method is particularly design for determination of paracetamol dose especially in modifying electrode. This study aims to modified carbon paste electrode with molecularly imprinted polymer (MIP). Significant advantages of using MIP are the superior stability, low cost and ease of preparation. The poly (3-aminiophenol) film was prepared by cyclic voltammetry method and 3-aminophenol monomer in supporting electrolyte (HClO4) with and whitout presence of paracetamol molecule. The effect of paracetamol was seen at cyclic voltammogram was founded, where oxidation peak potential of poly (3-aminophenol) shifted to more cathodic potentials from 0.948 to 0.780 V, in presence of paracetamol. The Ipa showed a good linear relationship with concentration in the range 0.01–0.1 mM, and the detection limit was 4,63 μM.